Effect of excess water on the desilylation of oligoribonucleotides using tetrabutylammonium fluoride. - Hogrefe, R I (1993)
The most commonly available 2' hydroxyl protecting group used in the synthesis of oligoribonucleotides is the tert-butyldimethylsilyl moiety. This protecting group is generally cleaved with 1 M tetrabutylammonium fluoride (TBAF) in tetrahydrofuran (THF). The efficiency of this reaction was tested on ribonucleotidyldeoxythymidine dinucleotides (AT, CT, GT, and UT). We have found that the efficiency of desilylation of uridine and cytidine is greatly dependent on the water content of the TBAF reagent. Conversely, the water content of the TBAF reagent [up to 17% (w/w)] had no detectable effect on the rate of desilylation of adenosine and guanosine. It was concluded that for effective desilylation of pyrimidine nucleosides the water content of the TBAF reagent must be 5% or less, which is readily achieved using molecular sieves. TBAF dried in such a manner was shown to be effective in deprotecting an oligoribonucleotide containing both purine and pyrimidine residues.